IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF BAHASA INDONESIA KELAS III SDN 2 SETU WETAN: Penelitian Tindakan Kelas - Khoerunissa; Kholid; Asih Wahyuningsih; Nita Fauziyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The learning outcomes in the Indonesian language subject are still low; based on the exam results conducted among 30 students, only 43,33% achieved the Minimum Competency Criteria (KKTP), while 56,67% have not yet completed the requirements. This research aims to improve the cognitive learning outcomes of students through the implementation of differentiated learning with a Culturally Responsive Teaching (CRT) approach in the Indonesian language subject for third-grade students at SDN 2 Setu Wetan. Through differentiated learning using CRT, students will gain meaningful learning experiences that take into account their cultural identities. This research was conducted from February 11 to 25, 2025, using the Classroom Action Research (PTK) method. The data collection techniques used include interviews, observations, documentation, and tests. The test sheets used consist of pre-test and post-test sheets. The results of the study indicate a significant improvement in learning outcomes, with an average of 70% in Cycle I and an increase to 90% in Cycle II. Thus, it can be concluded that the implementation of differentiated learning with a Culturally Responsive Teaching approach is an effective strategy for improving the cognitive learning outcomes of students in the Indonesian language subject.